Livelihood as a Part of Ecosystem - Thapa, Laxmi (Journal of Development Review, 2023)
The earning practices of rural residents have been transitioning from agricultural-based to a remittance-based economy. Data report that more than seventy five percent of population households in the study area are currently engaged in foreign employment. This phenomenon has had variety of impacts on both community and its ecological environment. However, academic discourse rarely delves into the changing dynamics of livelihood patterns and their interplay with the surrounding environment. This paper aims to examine the livelihood practices of people as a part of ecology. For the analysis of the objectives set here, mixed method has been deployed to collect and analyze the required data. Semi-structured interview is followed by observation as techniques to collect the information. The study reveals that the changing practice of the livelihood of the people has played a vital role to transform the operation modality of households in both the socio-economic and the physical, environmental dimensions. Moreover, from the analysis of collected data, it was found that the quantity of flora and fauna has increased significantly. The areas once utilized for grazing livestock and cultivation have been found to be rapidly transformed into overgrown and abandoned fields, as the lack of manpower has made it difficult to tend to the land used by the people. Thus, the study concludes livelihood as an integral part of ecology, continuously interacting with its surroundings and changes in its nature have also led to corresponding alterations in the size of components in ecosystem.